Toward a Theology of Engagement a Study of Komunitas Tritunggal Mahakudus as a Field of Action - Martinus Joko Lelono; Fatimah Husein; Leonard Chrysostomos Epafras (P3TK, Sanata Dharma University, 2020)
In his Apostolic Exhortation, Evangelii Gaudium (The Joy of the Gospel), for the Bishop, Clergy, Consecrated Persons, and the Lay Faithful on the Proclamation of the Gospel in Todays World, Pope Francis emphasized on the need to approach the young people, either to evangelize and educate them or the urgency to exercise greater leadership (Art. 106). Pope Francis encouraged the Catholic Church to regard these youth do not only as object but also the subject of evangelization. Komunitas Tritunggal Mahakudus, one kind of Catholic Charismatic Renewals in Indonesia, puts intensive programs to engage the youth in the evangelization work. With a well design programs, they achieve voluntary youth involvement. The present paper is an analysis of a negotiation process of Komunitas Tritunggal Mahakudus toward the present situation of the Catholic Church in Indonesia. From the perspective of Social Action Field theory, this analysis provides us with an insight of engaging youth in the evangelization efforts.DOI: doi.org/10.24071/jaot.2020.020104